The ‘Bounce Back’ rehabilitation programme for stroke survivors in South Africa – a case report - Laeeqa Sujee; Sacha Hildebrandt; Amy Harrison; Christa Matjekane; Thabiso Mmoledi; Sonti Pilusa; Kganetso Sekome; Adedayo T. Ajidahun (South African Journal of Physiotherapy)
Introduction: Stroke is one of the global leading causes of disability, with a higher prevalence at a younger age in sub-Saharan Africa. Returning to functional status is a primary goal of rehabilitation for stroke survivors. However, the cost of intensive rehabilitation is often a barrier for the under-resourced in South Africa.